The nature of employee engagement: rethinking the employee–organization relationship. Issue 3 (4th February 2017) - Eldor, Liat; Vigoda-Gadot, Eran
Abstract: Research interest in the new concept of employee engagement has grown dramatically in recent years. Employee engagement represents a work-related state of mind characterized by feelings of vigor, fulfillment, enthusiasm, absorption and dedication. However, scholars are still ambivalent about its theoretical contribution to explaining the employee–organization relationship. The goal of the study is to strengthen the theoretical foundation of the employee engagement concept in light of this relationship. We first compared employee engagement to other close concepts such as psychological empowerment and psychological contract. We then examined its contribution to the explanation of work centrality over and above psychological empowerment and psychological contract. Our study is based on an interactive sample of 593 employees from both private and public organizations in Israel. Our findings demonstrate that employee engagement is distinct from psychological empowerment and psychological contract and has an incremental value for work centrality over and above psychological empowerment and psychological contract. Implications of our findings are discussed the light of the employee–organization relationship.